On the numerical solution of the inverse elastography problem for time-harmonic excitation - Serranho, Pedro (2022)
In this paper we address the numerical solution of the inverse elastography problem, from the knowledge of the excitation field on the boundary and the displacement field in a grid of points within the domain. We suggest using a representation of the solution by the method of fundamental solutions and using a Newtontype method to iteratively approximate the Lam´e coefficients of the medium from elastography displacement measurements. We consider a toy model to illustrate the performance of the method.